Systematic literature review: stress among school counsellors - Mohammad Hanafi, Nor Hafizah; Che Amat, Muhammad Asyraf; Engku Kamarudin, Engku Mardiah (Science Research Society, 2023)
School counselor (GBK) is a career that carries out its duties as a teacher in providing guidance and counseling services in schools. This career is one of the important areas of work in the process of educating and providing auxiliary services in schools, but it is also not spared from many challenges and stresses. It is important that we examine the stress among GBK as it can affect their personal well-being, productivity and quality of service. Therefore, this systematic literature review (SLR) wasconducted with the aim of identifying stress factors among GBK. The study was conducted by obtaining data and findings from reading materials through search engines such as Scopus, Sage and Eric. The results of the analysis found that there are several factors that trigger stress among GBK and they have been grouped into two main factors, namely personal and profesional factors. Although there are studies done on the stress factor of GBK, it is still not conducted in depth, especially in the country. Therefore, it is hoped that the relevant studies in this field can be further enhanced in the future.